Questioning the Credibility of Foreign Researchersâ Findings in Respect of the Identity Politics of Balinese People - Wijaya, Nyoman (International Research Journal of Management, IT & Social Sciences, 2016)
There are two main issues raised in this article i.e.: what can be contributed by history through scientific biographical approach in defining the closest reasons of theÂ  implementation ofÂ  `Eka Dasa Rudra Ceremony` at Besakih Temple in 1963? This issue is very important to be set forward due to the tendency of the foreign researchers who wrote on this topic; they tried to find out the reasons which were far beyond; therefore the related reasons became neglected. Further, what can be contributed by the biographical approach towards humanities and social science? Applying the biographical approach, the previous historians who were just as the consumers of the theory then they are able to open a new path to humanities and show the premises of theories of the critical social sciences taking place unconsciously in social practices.